2009
DOI: 10.5483/bmbrep.2009.42.9.561
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the association of peroxidases with the antioxidant effect of p-coumaric acid in endothelial cells exposed to high glucose plus arachidonic acid

Abstract: Although many plant-derived phenolic compounds display antioxidant effects in biological systems, their mechanism of action remains controversial. In this study, the mechanism by which p-coumaric acid (p-CA) performs its antioxidant action was investigated in bovine aortic endothelial cells under oxidative stress due to high levels of glucose (HG) and arachidonic acid (AA), a free fatty acid. p-CA prevented lipid peroxidation and cell death due to HG+AA without affecting the production of reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It has a potent antioxidant activity, which has been demonstrated in cultured cells [7] and animal models [8,9]. Recent studies including those of our laboratory have revealed attractive properties of PCA as a potential hypopigmenting agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a potent antioxidant activity, which has been demonstrated in cultured cells [7] and animal models [8,9]. Recent studies including those of our laboratory have revealed attractive properties of PCA as a potential hypopigmenting agent.…”
Section: Introductionmentioning
confidence: 99%
“…bromide (MTT) [7,27]. Percent inhibition of a test sample against the UVB-induced viability loss was calculated as (C -B) / (B -A) × 100 where A is the viability of the non-irradiated vehicle control group, and B and C are the viabilities of the UVB-irradiated test (C) and vehicle control (B) groups.…”
Section: Uv Spectrophotometrymentioning
confidence: 99%
“…More and more evidence is accumulating that the consumption of grape and grape extracts and/or grape products rich in polyphenols, such as those found in red wine, is beneficial for the prevention of chronic degenerative diseases such as, cardiovascular disease 22 . Lee et al 21 have investigated the antioxidant action mechanism of p-coumaric acid in stressed bovine aortic endothelial cells and revealed that pretreatment with p-coumaric acid causes an induction of peroxidase and prevents lipid peroxidation and cell death caused by high glucose plus arachidonic acid exposure. Caffeic acid and cinnamic acid are reported to promote the insulin receptor tyrosyl phosphorylation, which upregulates the expression of the insulin signal associated proteins, increases the uptake of glucose, and alleviates insulin resistance in cells as a consequence 17 .…”
Section: Inhibition Kinetics Of Phenolic Acids On Pectin Methyl Esterasementioning
confidence: 99%
“…The phenol/peroxidase reaction has been generally regarded as a mechanism by which the pro-oxidant activity of natural polyphenols is mediated in animal cells (Galati et al 2002). However, it has been suggested that MPO may be involved in the antioxidant activity of phenolic compounds in endothelial cells under oxidative stress (Lee et al 2009). Therefore, one must be aware that honey is a very complex mixture containing numerous phenolic components that could modulate the activity of MPO.…”
Section: Discussionmentioning
confidence: 99%